Experiment and Failure Analysis of Rock-Like Material Affected by Different Excavation Depths - Yuan Tian; Zhende Zhu; Xinyu Liu; Yanxin He (Shock and Vibration)
In order to increase the understanding of the strength and failure mechanism of rock mass during tunnel excavation, a series of uniaxial compression tests were conducted on mortar specimen with cracks and holes by using a rock mechanics servo-controlled testing system. And by monitoring the experimental process, the initiation, propagation, and coalescence process of cracks were observed and characterized. According to the experimental results, the influences of the excavation depth on the mechanical parameters and fracture characteristics of mortar specimens with single hole and the ones with single-hole crack were analyzed in detail. In the specimens with single hole, the peak strength decreases with the increase of hole depth, but the peak strain and elastic modulus have no obvious linear correlation with the hole depth. And the position and angle of initial crack change differently with the increase of the hole depth. The position of initial crack moves from the side of the hole to the top of the hole. When the hole depth exceeds 50%, the crack initiation angle is no longer inclined to the axial stress direction, but parallel to the axial stress direction. In the specimens with single prefabricated crack, the wing-shaped secondary cracks are generated at the tip of the precrack, and the antiwing-shaped secondary cracks are generated at the tip when approaching the peak stress. However, in the specimens with single-hole crack, no antiwing-shaped crack appears. And when the hole depth reaches 80%, two wing-shaped cracks appear at the precrack tip. One of the new wing-shaped cracks appears in the direction of the extension line of the precrack.